2002
DOI: 10.1111/j.1095-8649.2002.tb01753.x
|View full text |Cite
|
Sign up to set email alerts
|

First record of the paedomorphic goby Schindleria praematura, Easter Island, South Pacific

Abstract: Thirty-five larvae and adults of the paedomophic goby Schindleria praematura were collected around Easter Island, during November 1999. Mean abundance from the five stations where they were caught (n=26) was 10·2 6·1 individuals 1000 m 3 . They occurred only in shallow areas. Oocyte counts ranged from 70 to 110. Otolith examination suggests that adults appear to live no longer than 3 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 2 publications
(2 reference statements)
1
9
0
Order By: Relevance
“…2). This pattern has been observed in other larval creediids (Leis, 1982) and in most coastal shallow water species from Easter Island (Castro & Landaeta, 2002; Landaeta et al ., 2002, 2003). There were no differences between the larval abundance on the leeward (south‐east) and windward sides of the island, nor in larval abundance from day and night catches (Kruskal–Wallis test, P > 0·05).…”
Section: Range Of Body Length (Notocord Length In Preflexion and Flexsupporting
confidence: 72%
See 1 more Smart Citation
“…2). This pattern has been observed in other larval creediids (Leis, 1982) and in most coastal shallow water species from Easter Island (Castro & Landaeta, 2002; Landaeta et al ., 2002, 2003). There were no differences between the larval abundance on the leeward (south‐east) and windward sides of the island, nor in larval abundance from day and night catches (Kruskal–Wallis test, P > 0·05).…”
Section: Range Of Body Length (Notocord Length In Preflexion and Flexsupporting
confidence: 72%
“…Larval S. praematura have 13 segmented caudal rays and inflexion occurs at a very small size ( c . 3·5 mm)(Leis & Trnski, 1989; Landaeta et al ., 2002).…”
Section: Range Of Body Length (Notocord Length In Preflexion and Flexmentioning
confidence: 99%
“…Kon & Yoshino (2002) and Kon et al (2007) stated that the Schindleriidae includes one of the smallest and youngest reproducing vertebrates (average 37 days old). Landaeta et al (2002) also found that Schindleria praematura (Schindler) is a fast‐growing fish with a very short life span (no more than 2 or 3 months) based on otolith analysis. Schindleriids have been recorded from the reef habitats in many areas of the Indo‐Pacific oceans, including: southern Japan, south China (Ozawa & Matsui, 1979), Hawaii (Schindler, 1930, 1931; Leis, 1982; Clarke, 1991), Tahiti, Samoa and the Tasman Sea (Bruun, 1940), Great Barrier Reef (Leis, 1994), Laccadine Islands off south‐eastern India (Jones & Kumaran, 1964), south‐eastern Africa (Harris & Cyrus, 1996), and Salas Y Gomez (Belyanina, 1989; Parin et al , 1997) and Easter Island (Landaeta et al , 2002) in the south‐eastern Pacific.…”
Section: Comparison Between the Three Nominal Species Of The Schindlementioning
confidence: 96%
“…17 mm in average 6 ), and have paedomorphic features (i.e., never undergoing metamorphosis and retaining a larval phenotype throughout their life 2 ). Therefore, they are generally overlooked or mistaken for larval fishes 7 , 8 and most studies are based on very few samples or report the sightings of some individuals as bycatch of other research purposes (mainly from light traps and planktonic tows) 9 , 10 . More recent sampling efforts 5 , 11 and the inspection of museum collections from plankton tows for the presence of Schindleria 12 have increased knowledge and attention on the presence and distribution of this genus, and high numbers of these fishes have increasingly been studied.…”
Section: Introductionmentioning
confidence: 99%